(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research discusses the effect of the mandatory application of SNI and ISO for Textiles and Textile Products (TPT) on the export and import of Indonesian TPT with data for the period 2010-2019 using the Econometric Model Analysis (Fixed Effect Model) and the OLS Method using multiple regression analysis. The variables used are the total volume of imported TPT and the total volume of TPT exports. The independent variables are real GDP, real exchange rate and the dummy of mandatory application of SNI and ISO for Textiles and Textile Products to Indonesian textile and textile products and imports. The results of this study indicate that there is a positive influence between the mandatory application of SNI and ISO for Textiles and Textile Products on Indonesian TPT Exports and Imports, and provides an analysis of the impact of Indonesian government policies in making regulations on the textile and textile product industry in Indonesia. Economic policies are still needed, such as economic incentives, such as lowering bank interest rates for investment and a relatively stable Rp/US exchange rate that will help textile producers in calculating raw material costs and profits.